EFFECT OF INTRACAMERAL IMPLANTATION OF PLASMA-MODIFIED POLYLACTIC ACID FILMS ON THE COURSE OF IN VIVO-INDUCED BULLOUS KERATOPATHY - E.O. FILIPPOVA; N.M. IVANOVA; V.F. PICHUGIN (Avicenna Tajik State Medical University, 2021)
Objective: To determine the effect of intracameral implantation of polylactic acid (PLA) films modified in low-temperature atmospheric pressure plasma on the course of in vivo-induced bullous keratopathy (BK). Methods: In vivo experiments were performed on 14 Sylvilagus bachmani rabbits divided into 4 groups: intact; a disease model group; a group of animals with induced BK and after a course of conservative treatment; a group of animals with induced BK, after implantation of PLA films into the anterior chamber and conservative treatment. Results: According to the data obtained, in the group of animals with a PLA film implanted into the anterior chamber, after plasma exposure, new vessels are formed, and leukocytes with a specific volume of no more than 3.7% are infiltrated closer to the posterior boundary membrane. Leukocyte infiltration, represented by lymphocytes and mast cells, is the reaction of the cornea to artificial material, as well as the course of the primary alteration - the inflammatory process due to the induction of the disease. Electron microscopic data (there are many polysomes and microvesicles in the cytoplasm of lymphocytes) indicate the intensified activity of immune defense cells. The appearance of blood vessels is another sign of the course of inflammation in the cornea, caused by BK. Moreover, vessels with a volume of up to 6% were found in all groups with induced disease, which indicates the absence of the effect of material implantation on vasculogenesis. Conclusion: Films based on PLA have properties close to hydrophobic, the effect of plasma decreases the contact angle and increases the values of surface energy to a greater extent due to the polar component, bringing the properties of the material closer to hydrophilic. Implantation of PLA films treated with plasma and sterilized by γ-radiation into the anterior chamber of the eye in induced BK does not aggravate the disease process and can be taken into the further development of the material for creating a corneal implant from it.